2006
DOI: 10.1037/0097-7403.32.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the displacement of objects: A series of tasks with great apes (Pan troglodytes, Pan paniscus, Gorilla gorilla, and Pongo pygmaeus) and young children (Homo sapiens).

Abstract: The authors administered a series of object displacement tasks to 24 great apes and 24 30-month-old children (Homo sapiens). Objects were placed under 1 or 2 of 3 cups by visible or invisible displacements. The series included 6 tasks: delayed response, inhibition test, A not B, rotations, transpositions, and object permanence. Apes and children solved most tasks performing at comparable levels except in the transposition task, in which apes performed better than children. Ape species performed at comparable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
157
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(172 citation statements)
references
References 43 publications
15
157
0
Order By: Relevance
“…Research also indicates that most Piagetian invisible displacement tasks with some form of control can be solved by all great ape species [Barth & Call, 2006;Call, 2001;Collier-Baker et al, 2006;de Blois et al, 1998]. Gibbons and marmosets have been tested on invisible displacement controls [Fedor et al, 2008;Mendes & Huber, 2004]; however, small sample sizes and high individual variability in performance makes it difficult to come to firm conclusions about these species' understanding of invisible displacements.…”
Section: Introductionmentioning
confidence: 96%
“…Research also indicates that most Piagetian invisible displacement tasks with some form of control can be solved by all great ape species [Barth & Call, 2006;Call, 2001;Collier-Baker et al, 2006;de Blois et al, 1998]. Gibbons and marmosets have been tested on invisible displacement controls [Fedor et al, 2008;Mendes & Huber, 2004]; however, small sample sizes and high individual variability in performance makes it difficult to come to firm conclusions about these species' understanding of invisible displacements.…”
Section: Introductionmentioning
confidence: 96%
“…The experimenter then hides a toy inside one of them and rotates the platform. Although 30-month-old children have been found to perform above chance (on average) when the object is rotated 180º (Barth & Call, 2006), if one discounts accurate searches directed at the center occluder (which remains in its original position when the platform is rotated), the children generally perform at levels below chance. Several great ape species perform similarly when tested with the 180º rotation (Barth & Call, 2006).…”
mentioning
confidence: 99%
“…Although 30-month-old children have been found to perform above chance (on average) when the object is rotated 180º (Barth & Call, 2006), if one discounts accurate searches directed at the center occluder (which remains in its original position when the platform is rotated), the children generally perform at levels below chance. Several great ape species perform similarly when tested with the 180º rotation (Barth & Call, 2006). Similarly, Fiset (2007) found that when two identical occluders are placed on either end of a rotating beam, and a hidden toy is displaced by 180º, dogs perform at or below chance (see also Bai & Bertenthal, 1992, for similar results with children).…”
mentioning
confidence: 99%
“…Research also indicates that among nonhuman animals, only the great ape species (orangutans, gorillas, bonobos, and chimpanzees) can solve single invisible controls and adjacent double invisible displacements without the use of associative strategies (de Blois et al 1998;Call 2001;Barth and Call 2006;CollierBaker and Suddendorf 2006). Similar success has been documented in 19-, 26-, and 30-month-old children, who were tested on the same tasks used with nonhuman primates (Call 2001;Barth and Call 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Research to date indicates that Piagetian visible displacement tasks with some form of control can be solved by all great ape species (Natale 1989;de Blois et al 1998;Call 2001;Barth and Call 2006), one gibbon (Fedor et al 2008), several monkey species (e.g., Natale 1989;de Blois and Novak 1994;Neiworth et al 2003), a few lemur species (Deppe et al 2009), domestic cats and dogs (see Dumas 1987 andGoulet 1998 for reviews), and bottlenose dolphins (Jaakkola et al 2010). Research also indicates that among nonhuman animals, only the great ape species (orangutans, gorillas, bonobos, and chimpanzees) can solve single invisible controls and adjacent double invisible displacements without the use of associative strategies (de Blois et al 1998;Call 2001;Barth and Call 2006;CollierBaker and Suddendorf 2006).…”
Section: Introductionmentioning
confidence: 99%